Full-duplex device-to-device communications:key technologies and prospects - Jiaxin DING; Daquan FENG; Gongbin QIAN; Nan ZHANG (Dianxin kexue)
Due to the physical proximity,D2D communications can bring proximity gain,reusing gain and hop gain,and thus can potentially increase system spectral-efficiency and energy-efficiency.Full-duplex D2D communications,which enable the transceiver to simultaneously transmit and receive in the same band,can further improve the system performance.Therefore,full-duplex D2D communications has being considered as one of the key techniques in the next generation cellular networks.The features of full-duplex D2D communications and the significance in 5G systems were briefly introduced as well as its applications.Then,the state-of-art research on full-duplex D2D resource allocation was presented and discussed.Finally,some research topics that deserve further study was outlined and concluded.